Upravlenie formirovaniem tsennosti orientatsii u khokkeistov v protsesse sportivnoi podgotovki i sorevnovatel'noi deyatel'nosti - Fomin, N. A.; Lyapkalo, V. N. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
In this paper authors tried to show the importance and necessity in managing of value orientations forming in athletes. There are sharp contradictions arising between youth's need to join popular kinds of sport and financial difficulties to actualize it, between the salary level of; in this case, professional hockey-player and wish of high-developed athlete to stay with his amateur, low incoming team. The results of the present experimental research inquire, that special activity oriented to value orientations forming was followed by improvement of the game quality and the unity of on ice-hockey team.